PENGARUH PEMBERIAN DEEP BREATHING EXERCISE TERHADAP SATURASI OKSIGEN PADA PASIEN PPOK DI IGD RSUD SANJIWANI GIANYAR TAHUN 2018 - I Made Mertha (Jurnal Gema Keperawatan, 2018)
The purpose of this study is to determine the effect of giving deep breathing exercise to oxygen saturation in COPD patients in the Emergency Unit of Sanjiwani Hospital Gianyar on 2018. The research design was quasy experiment with pre and post test with control group using purposive sampling method to 20 respondents which grouped into two groups. There are 10 respondents in treatment group and 10 respondents in control. The result of Paired T-test of treatment group, mean difference 5,1% with ρ value 0,001. Of control group mean difference of 0.5% with ρ value 0,052. The conclusion showed there is a significant effect of deep breathing exercise to COPD patients.